DIGITAL TECHNOLOGIES AND THEIR IMPACT ON HUMAN BEHAVIOR (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article examines the multifaceted and complex influence of digital technologies on human behavior, psychological state, cognitive processes, and the system of social relations from both a scientific-theoretical and empirical perspective. Due to the rapid development of information and communication technologies, almost all areas of human activity have become integrated with the digital environment, leading to significant transformations in individuals’ thinking patterns, decision-making mechanisms, modes of communication, and social adaptation strategies.
Keywords: Digital technologies, human behavior, psychological impact, cognitive development, social networks, virtual environment, information flow, digital addiction, communicative processes, media literacy.